ICT-Based Arabic Learning: A 21st Century Learning Innovation (Pembelajaran Bahasa Arab Berbasis ICT: Sebuah Inovasi Pembelajaran Abad 21) - Abdul Muid (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2024)
This research reveals innovations in Arabic language learning based on information and communication technology (ICT) in the 21st Century. The main focus of this study is to know and analyze innovations in Arabic language learning based on ICT. This study used a descriptive-analytical approach. The literature study method, also known as content analysis, uses the review and analysis of primary sources such as books, scientific journals, articles, and documents related to the topic. The results showed that Arabic learning innovations based on information and communication technology (ICT) were considered by teachers as new ideas and approaches. Teachers see ICT as a tool to solve problems and achieve learning objectives. Therefore, the role of teachers in using ICT to develop innovation and learning media is very important.